1992
DOI: 10.1146/annurev.ph.54.030192.003051
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrobiosis

Abstract: We believe we have established the major principles governing the stabilization of living cells in the unique condition known as anhydrobiosis. These findings have permitted us to design ways to stabilize membrane vesicles, liposomes, and proteins, and perhaps eventually even intact cells that do not normally survive dehydration. In a complex phenomenon as ancient as anhydrobiosis, one would expect a myriad of adaptations to be required for survival of drying. But the arguments presented here suggest that a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
864
1
22

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,273 publications
(902 citation statements)
references
References 0 publications
15
864
1
22
Order By: Relevance
“…It has been suggested, therefore, that trehalose plays a role as a stabiliser of cellular structures under stress conditions (Keller et al, 1982;Crowe et al, 1984). In accordance with this suggestion, in vitro studies have revealed the exceptional capability of trehalose in protecting biological membranes and enzymes from freezing-or drying-induced dehydration (for a review see Crowe et al, 1992) and heat stress (Hottiger et al, 1994).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been suggested, therefore, that trehalose plays a role as a stabiliser of cellular structures under stress conditions (Keller et al, 1982;Crowe et al, 1984). In accordance with this suggestion, in vitro studies have revealed the exceptional capability of trehalose in protecting biological membranes and enzymes from freezing-or drying-induced dehydration (for a review see Crowe et al, 1992) and heat stress (Hottiger et al, 1994).…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, trehalose synthesis is induced in most of these organisms in response to a small set of specific environmental conditions. In particular, trehalose is accumulated in phases of nutrient starvation, desiccation, and after exposure to a mild heat shock (for reviews see Van Laere, 1989;Wiemken, 1990;Crowe et al, 1992). It has been suggested, therefore, that trehalose plays a role as a stabiliser of cellular structures under stress conditions (Keller et al, 1982;Crowe et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Although severe loss of water is often detrimental to life, some invertebrate animals from a few phyla have developed mechanisms to cope with extreme desiccation by entering a state known as anhydrobiosis (Clegg, 2001;Crowe and Clegg, 1973;Crowe et al, 1992;Keilin, 1959;Watanabe et al, 2005). Anhydrobiotic organisms possess the ability to survive desiccation in nature to water contents around 0.02 -0.05 g H 2 O g -1 dry mass and enter into a state that approaches suspended animation (Clegg, 1973;Madin, 1974, 1975;Hinton, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Anhydrobiotic organisms possess the ability to survive desiccation in nature to water contents around 0.02 -0.05 g H 2 O g -1 dry mass and enter into a state that approaches suspended animation (Clegg, 1973;Madin, 1974, 1975;Hinton, 1968). Desiccation tolerance has also been observed in some flowering plants, algae, fungi, bacteria, and most seeds of higher plants are desiccation tolerant (Billi and Potts, 2002;Crowe et al, 1992;Hoekstra et al, 2001;Potts, 1999). In the study…”
Section: Introductionmentioning
confidence: 99%
“…For other organisms, exposure to these environmental stresses induces lethal damage to cells, and tardigrades must therefore possess a way to either protect their cells from damage, or efficiently repair damage that arises. Most of the early work on mechanisms of desiccation tolerance was directed towards studies on membrane stabilization molecules (Crowe et al, 1992;Crowe, 2002). More recent research has had a general molecular approach on detecting differences between animals in the desiccated (anhydrobiotic) and the hydrated states, in order to reveal the molecular and physiological mechanisms behind the tolerance Reuner et al, 2010;Rizzo et al, 2010;Wełnicz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%